Synthesis, Characterization and Electrochemical Study of Transition Metals [Cu(II), Fe(III)] Complexes of Fumarate 2,9-Dimethyl-1,10-phenanthroline - CHU, QINGZHU; ZHANG, MEILING; DING, CAIFENG (Asian Journal of Chemistry, 2010)
Two new complexes containing 2,9-dimethyl-1,10-phenanthroline (phen), fumarate and transition metals, Cu2(phen)2(fumarate)(H2O)2]Cl2 (1), [Fe2(phen)2(fumarate)(H2O)2](NO3)4 (2), were synthesized and characterized. The crystal structure of compound 1 was determined by X-ray crystallography. The thermal decomposition was studied by thermal analysis TG-DTG. The interaction of these complexes with DNA was studied by cyclic voltammetry (CV) and differential pulse voltammetry (DPV). The electrochemical experimental results indicate that these complexes could interact with DNA.